Evaluation of Daylight Intensity for Sustainbility in Residential Buildings in Cantonment Cottages Multan - Yousuf, Sumra; Alamgir, Sabahat; Afzal, Muhammad; Maqsood, Sohail; Arif, Muhammad Salaar (Mehran University Research Journal of Engineering and Technology, 2017)
Day lighting is a useful and effective source of energy savings and visual comforts in buildings. Occupants expect good daylight in their living spaces for better living environment. The quality and quantity of natural light entering in to a building depend on both internal and external factors. Daylight strategies basically depend on the accessibility of natural light that is determined by the latitude of the building site and the conditions surrounding the building. Daylight provides lighting energy and energy demand reduction during peak utility hours. Bringing daylight into a building that displaces electric lighting and provides sufficient illumination is the greenest way to light a building presently. This research, aims at analyzing the daylight intensity in residential buildings in Cantonment Cottages Multan which is one of the hottest and progresse city of Pakistan. The intensity of daylight can be expressed in the terms of luminance and daylight factor. In this research, the 5 and 7 marla houses in Cantt Cottages in Multan were selected. The device lux meter was used for measuring intensity with which the brightness appears to the human eye. The readings were taken by placing Lux Meter at the center and near windows in each building component at 2-4 pm. Inorderto evaluate the daylight intensity, the measured luminance in each component of building is compared with the standard illuminance as per recommendation of CIBSE (Chartered Institute of Building Service Engineers). After investigation, it has been found that daylight factor is much higher than the standard values in east and west oriented building components whereas the building components oriented in north and south, the day light factor is little higher than standard values as per recommended by CIBSE. The design parameters including building orientation, glazing area, room size to window opening ratio etc. is not appropriate with respect to sustainable design